2004
DOI: 10.1002/pds.1048
|View full text |Cite
|
Sign up to set email alerts
|

Impact of regulatory labeling for troglitazone and rosiglitazone on hepatic enzyme monitoring compliance: findings from the state of Ohio medicaid program

Abstract: Regulatory actions had only modest effects on the incidence of liver monitoring. More effective and timely communication strategies, health provider prescribing interventions and modification of health provider behaviors to enhance compliance with recommended risk management measures need to be identified, evaluated and implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 14 publications
2
46
0
Order By: Relevance
“…The present findings are compatible with other studies that demonstrated lack of full adherence to drug safety recommendations in performing tests to monitor adverse effects in clinical practice (35,36).…”
Section: Limitations and Strengthssupporting
confidence: 92%
“…The present findings are compatible with other studies that demonstrated lack of full adherence to drug safety recommendations in performing tests to monitor adverse effects in clinical practice (35,36).…”
Section: Limitations and Strengthssupporting
confidence: 92%
“…A similarly poor impact of communication strategies has previously been reported [8][9][10][11][12][13][14] but this study goes further than previous ones by illustrating the limited capacity of such a strategy to inform health professionals. The difficulty in the present case was to disseminate a safety warning concerning medicines systematically prescribed to all infants and young children but also available without prescription and more often perceived as vitamin supplements than as medicines by the public.…”
Section: Discussionsupporting
confidence: 49%
“…Mailings to prescribers have little impact on prescribers' behavior. [9][10][11] Several venues for black box warning information include the FDA Web site and a free Web site dedicated to providing a list of medications with warnings. 5 The identification of effective methods to disseminate information regarding black box warnings requires further study.…”
Section: Discussionmentioning
confidence: 99%